(untitled) - CURRY, DEAN (USA, 1988)
1.Chef / 2.Bus driver / 3.Boy scout leader/ 4.Circus fat lady / 5.Student / 6.Waiter / 7.Ballet dancers / 8.Tennis player / 9.Rancher / 10.Motorcycle fans / 11.Television cameraman / 12.Musician / 13.Soccer player / 14.Golfer / 15.Famer / 16.Telephone operator / 17.Legal secretary / 18.Government secretary / 19.Teacher / 20.Tv repairman / 21.Bridge players / 22.Research scientist / 23.Fork lift operator / 24.Fireman / 25.Welder / 26.Auto mechanic / 27.Lifeguard / 28.Corporation executive / 29.Train conductor / 30.Rodeo rider / 31.Oil field worker / 32.Policeman / 33.Judge / 34.Chemist / 35.Disc jockey / 36.Taxicab driver / 37.Nurse / 38.Grocery checker / 39.Coin collector / 40.Photographer / 41.Telephone lineman / 42.Engineer / 43.Architect / 44.Magician / 45.Surgeon / 46.Pool player / 47.Sales manager / 48.Wrestler / 49.Postman / 50.Artist / 51.A grandmother's dolls / 52.Jockey / 53.Verb list
Keywords: INGLES